Fundamentals of Entrepreneurship ENT300 The Soapranos / Noor Ashyikin Jamali… [et al.] - Jamali, Noor Ashyikin; Sarkawi, Fatin Amalina; Abang Abdul Rahman, Dayang Nur Khairunnisa; Hassan, Nur Hafizah; Yaman, Yasirah Nuratiqah (2015)
The project we want to propose is a service which is housecleaning. We have chosen to be known as The Soapranos Housecleaning Enterprise. We choose this name because we believe that it will attract and get a good response from our customers. We provide our customers with a proper standard of cleaning and multi services. So, we have to ensure that our services will meet up the expectation of our company name. It is our priority to provide the best and quality services for our customers. The name given is to create an impression to the customer where it will make them feel we are here to help them to create comfortable and secure environment.